Perception of products of landscape painting us the factor of formation of art-aesthetic experience of students - I.H. Bryzhata (Academy of Cognitive and Natural Sciences, 2006)
Article is devoted to a problem of formation of the creative person of the future teacher of disciplines of art. Approaches to formation of art-aesthetic experience of students are proved by perception ofproducts of landscape pointing, and also mechanisms of this process are opened